Creases - Priemus, Jessica (2015)
Creases is a nineteen-piece capsule collection, designed to draw attention to the quality of the textiles used. Creases, folds, imperfections and references to raw materials are all expressed through intricate hand embroidery patterns and bold appliqué graphics. Rather than relying on an additional written narrative, the garments reference themselves.